Metode dan Corak Kitab Tafsir Al-Tafsir Al-Munir - Islamiyah Islamiyah (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2022)
The book of Tafsir al-Muni>r: fi> al-‘Aqi>dah wa al-Shari>’ah al-Manhaj is a contemporary commentary compiled by Prof. Dr. Wahbah az-Zuhaili. This book consists of 16 large volume, not less than 10,000 pages. According to prof. M. Ridlwan Nasir, so far there is often confusion in the use of term “manhaj” (method) with tendencies. Therefore, according to him, it necessary to describe the grouping of various methods according to their respective pressure points of points of view. From this approach, it can be concluded that the book of interpretation of al-Muni>r has 4 methods of presentation which are viewed from various different aspects, namely Iqtira>n, muqa>rin,tafsi>liy, and tahli>liy. This interpretation has advantages that can cover the flaws of shortcomings in this book for some people.